2016
DOI: 10.18632/oncotarget.12705
|View full text |Cite
|
Sign up to set email alerts
|

ALK FISH patterns and the detection of ALK fusions by next generation sequencing in lung adenocarcinoma

Abstract: Break-apart ALK FISH probe is the FDA approved approach for detection of ALK rearrangements in lung carcinoma patients who may benefit from ALK kinase inhibitors. The FISH assay can be technically challenging and difficult to interpret. ALK immunohistochemistry and next generation sequencing have been proposed as alternative approaches. In this study, we compared various ALK –FISH patterns to next –generation sequencing (NGS) for gene fusion detection, ALK immunohistochemistry (IHC) and tumor responses to criz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 37 publications
(41 reference statements)
3
43
0
Order By: Relevance
“…Alternatively, this case could be an example of the very rare occurrence of concurrent EGFR mutation and ALK translocation . Our group reported recently that some ALK FISH patterns, such as a single orange (5′ deletion) or ‘mixed patterns’ (a combination of single orange and split signal), are associated with higher discordance with ALK IHC and next‐generation sequencing for gene fusions, and that these cases are associated with a less favourable response to crizotinib …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, this case could be an example of the very rare occurrence of concurrent EGFR mutation and ALK translocation . Our group reported recently that some ALK FISH patterns, such as a single orange (5′ deletion) or ‘mixed patterns’ (a combination of single orange and split signal), are associated with higher discordance with ALK IHC and next‐generation sequencing for gene fusions, and that these cases are associated with a less favourable response to crizotinib …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, this case probably represents a false positive ALK FISH result. It has been shown recently that NGS studies might be of help in resolving discordant ALK status cases …”
Section: Discussionmentioning
confidence: 99%
“…DNA sequencing was performed using the Ion AmpliSeq Cancer Panel (Ion Torrent; Life Technologies, Thermo Fisher Scientific, Waltham, MA, USA), as reported previously . Briefly, 10 ng of DNA was amplified by polymerase chain reaction (PCR) using the AmpliSeq Cancer Panel Primers pool and Ion AmpliSeq Master Mix version 2.0.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Yamamoto and colleagues, RNA was extracted from cytologic specimens derived from fluid aspiration, namely, cerebrospinal fluid, pleural effusion, abdominal fluid, and pericardial effusion; and ALK fusion genes were detected in 2.4% of 365 patients . Various groups have used NGS to evaluate histologic samples of lung adenocarcinoma, mainly in cases of discordance between FISH and IHC results . For example, Jang et al analyzed 5 discordant cases using the HiSeq 2000 NGS platform (Illumina); 1 case was false‐positive on D5F3 IHC, and 3 of the 4 remaining cases were false‐positive on ALK FISH .…”
Section: Alk and Ros1 Rt‐pcrmentioning
confidence: 99%
“…Pekar‐Zlotin and coworkers analyzed 6 discordant cases using the Illumina platform (HiSeq 2000) and more often confirmed the IHC results (5 cases) than the FISH results (1 case) . By using the Ion Torrent NGS technology (Thermo Fisher Scientific), Dacic et al demonstrated that the ALK 5′ deletion (single red) signal was more frequently false‐positive than were the various FISH patterns . Notably, NGS can be used when crush and thermal artifacts impair the performance of FISH or IHC.…”
Section: Alk and Ros1 Rt‐pcrmentioning
confidence: 99%